Faktor Eksternal Dan Internal Terhadap Keputusan Kredit Oleh Nasabah Pada PT. Pegadaian Manokwari - Yuyun P. Rahayu (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2019)
Purpose of this study is to analyze the relationship between external and internal factors on credit decision making by the customers. This is an associative study using quantitative data. Population in this study is the customer of PT. Pegadaian Manokwari. Incidental techniques is used as sampling method with 100 customers as respondents. Data analysis in this study used ordinal logistic regression. The results indicate that the independent variables have partial influence on credit decisions at PT. Pegadaian Manokwari Regency. Variables that have a significant effect are the appropriateness of collateral value, ease of procedure and types of work for both civil servants and private employees as well as the average credit return for two months. Furthermore, the results also indicate that the more considerations will lead to the opportunity for the decision to take credit at PT. Pegadaian are getting higher and vice versa. Thus, collateral and procedures as an external factors and customer’s job and credit period as internal factors are significant factors at the 95% level of confidence affecting the customer’s credit decisions at PT. Pegadaian Manokwari.